The hobbit, or, There and back again - Tolkien, J. R. R. (John Ronald Reuel), 1892-1973. (London : HarperCollins, 2012)
Bilbo Baggins, a respectable, well-to-do hobbit, lives comfortably in his hobbit-hole until the day the wandering wizard Gandalf chooses him to take part in an adventure from which he may never return.
"The enchanting prelude to The Lord of the Rings"--Cover.
Adult.
Adult
Keywords: Baggins, Bilbo (Fictitious character) -- Fiction; Hobbits (Fictitious characters) -- Fiction; Middle Earth (Imaginary place) -- Fiction; Baggins, Bilbo (Fictional character) -- Fiction; Hobbits (Fictional characters) -- Fiction; Middle Earth (Imaginary place) -- Fiction; Fantastic fiction; Fantastic fiction